Psychological Security in late adolescence: an empirical study for a sample of students in the Faculties of Education and Economics In Hama University (Journal of Hama University, 2022)
The current research aimed at measuring the level of Psychological Security in late adolescence for a sample of students in the Faculties of Education and Economics In Hama University, It also aimed to recognize the most common dimensions of Psychological Security and to recognize the differences of the sample members grades on the scale of Psychological Security according to research variables (gender / specialization), The sample consisted of (204) male/ female students: 118 from Faculties of Education and 86 from Faculty Economics, The Psychological Security scale prepared by Fatima Oudi (2002) was used after making sure of its validity and reliability, The research had the following results:1.There is high level of Psychological Security in the sample as a whole.2.the third dimension (faith in Allah / Confidence in God) came first.3.thefifty dimension (Release of Psychological Pains) came fifth.4.there are no statically significant differences on the scale of Psychological Security and its dimensions according of the variables of the research (gender / specialization).